Trendek és tévhitek: Elemzés a görög felsőoktatás egy jellemzőnek hitt sajátosságáról - Barna, Ildikó; Himesi, Zsuzsa (Szociológiai Szemle, 2024)
In Greece the issue of education, or rather of higher education attracts the attention not only of Greek researchers, but in fact it is in the focus of the whole Greek society's thinking. After having read many articles on the issue, it was astonishing to see that though many authors said that there was considerable 'over-education' in Greece and that the country's enrolment ratios were significantly higher than expected on the basis of the level of its economic development, several of the data produced by them as proof were visibly poorly established, or if well-founded, they were based on a rather limited number of countries, selected in a way which made them completely impossible to explore. In this paper we aim at presenting surprising, and hopefully interesting findings of our analysis, based on statistical data, and employing different methods of testing.